Comparative transcriptomic and plastid development analysis sheds light on the differential carotenoid accumulation in kiwifruit flesh - Bhargava, Nitisha; Ampomah-Dwamena, Charles; Voogd, Charlotte; Allan, Andrew C. (Frontiers in Plant Science, 2023)
Carotenoids are colorful lipophilic isoprenoids synthesized in all photosynthetic organisms which play roles in plant growth and development and provide numerous health benefits in the human diet (precursor of Vitamin A). The commercially popular kiwifruits are golden yellow-fleshed (Actinidia chinensis) and green fleshed (A. deliciosa) cultivars which have a high carotenoid concentration. Understanding the molecular mechanisms controlling the synthesis and sequestration of carotenoids in Actinidia species is key to increasing nutritional value of this crop via breeding. In this study we analyzed fruit with varying flesh color from three Actinidia species; orange-fleshed A. valvata (OF), yellow-fleshed A. polygama (YF) and green-fleshed A. arguta (GF). Microscopic analysis revealed that carotenoids accumulated in a crystalline form in YF and OF chromoplasts, with the size of crystals being bigger in OF compared to YF, which also contained globular substructures in the chromoplast. Metabolic profiles were investigated using ultra-performance liquid chromatography (UPLC), which showed that β-carotene was the predominant carotenoid in the OF and YF species, while lutein was the dominant carotenoid in the GF species. Global changes in gene expression were studied between OF and GF (both tetraploid) species using RNA-sequencing which showed higher expression levels of upstream carotenoid biosynthesis-related genes such as DXS, PSY, GGPPS, PDS, ZISO, and ZDS in OF species compared to GF. However, low expression of downstream pathway genes was observed in both species. Pathway regulatory genes (OR and OR-L), plastid morphology related genes (FIBRILLIN), chlorophyll degradation genes (SGR, SGR-L, RCCR, and NYC1) were upregulated in OF species compared to GF. This suggests chlorophyll degradation (primarily in the initial ripening stages) is accompanied by increased carotenoid production and localization in orange flesh tissue, a contrast from green flesh tissue. These results suggest a coordinated change in the carotenoid pathway, as well as changes in plastid type, are responsible for an orange phenotype in certain kiwifruit species.